On the diet of two endemic and rare species of Trichomycterus (Ostariophysi: Trichomycteridae) in the Jordão River, Iguaçu River basin, southern Brazil - Barreto, Almir Petersen; Armiliato, Fabiane Cristina; Ribeiro, Vanessa Maria; Abilhoa, Vinícius (Estudos de Biologia, 2013)
The diet and the eect of body size on the feeding habits of Trichomycterus crassicaudatus and Trichomycterus stawiarski, collected in the Jordão River, an import tributary of the Iguaçu River basin, were investigated. Samples were collected in august 2003 during the Jordão River Energetic Complex Aquatic Fauna Rescue and Monitoring program. Stomach contents were evaluated through the frequency of occurrence, permutational multivariate analysis of variance (PERMANOVA), si-milarity percentage analysis (SIMPER) and non-metric multidimensional scaling analysis (MDS) methods. A total of 86 stomach contents of T. stawiarski and 36 of T. crassicaudatus were assessed. The species presented an insectivorous feeding habit, with differences in the diet composition of the “smallest” and the “largest” individuals. Ephemeroptera nymphs, lar-vae and pupae of Diptera, organic detritus and plant fragments were the most important food items. Both species feeding habits were based mainly in benthic aquatic immature insects.